Health interventions for the reduction of hospital readmission within 30 days in clinical patients: An integrative review (Research, Society and Development, 2022)
Study with the objective of analysing the evidence available in the scientific literature on the interventions used to reduce hospital readmissions within 30 days in clinical patients who were discharged from the hospital to the home. An integrative review was carried out on the online Medical Literature Analysis and Retrieval System and Latin American and Caribbean Literature in Health Sciences databases. Intervention research, published between January 2009 and April 2020, in Portuguese, English and Spanish, was included. The sample consisted of 71 articles. The most frequently performed interventions were telephone contact after discharge (73.2%), health education after discharge (71.8%) and health education during hospitalization (67.6%). Identification of readmission risk (12.9%), home visits after discharge (26.8%) and discharge planning (28.2%) were the least mentioned. The interventions were performed predominantly by a multidisciplinary team (39.5%). There was a significant reduction in readmissions in 50.7% of the studies. It was found that the interventions are aimed at preparing the patient during hospitalization for the return home and post-discharge monitoring to reinforce the care plans and clarify doubts, this important combination of different actions by the multiprofessional team impacts readmission rates.